Performing Islamic Identity on Instagram: A Multilingual and Multimodal Analysis of Pakistani Users’ Comments - Zia, Shanza (ACADEMIA International Journal for Social Sciences, 2025)
The rapid expansion of social media has transformed the ways in which religious identity, emotion, and community are constructed and negotiated in digital environments. This study examines how Pakistani Instagram users employ multilingual and multimodal resources to perform Islamic identity in public comment sections of Islamic content (Habib & Shahid, 2025). Grounded in a qualitative sociolinguistic framework, the research analyzes 66 comments collected from five Pakistani Instagram pages featuring Islamic reels. The study focuses on patterns of language use (Arabic, Urdu, and English), code-switching practices, and the deployment of emojis as multimodal markers of meaning.The results indicate that the primary characteristic of the discourse is the religious expression where English, as a motivational and reflective tool to help a person engage with the world of sacred authority and piety, Arabic offers a cultural resonance, and Urdu, as a reflection of the culture, is the most widespread. Code-switching becomes a strategic sociolinguistic option improving authentic and inclusive communications and increasing the audience (Ramaila, 2025). The use of emojis like hearts, prayer hands, and crying face adds intensity to emotions, commitment to the religion, and to performative religiosity. In addition to devotional expression, the comments often hold promise of hope, perseverance, moral reflection, and civilization. In other cases, the users do moral critique and interfaith appreciation showing how diverse and complex digital Islamic discourse can be.Instagram is suggested as an active location where religiosity is publicly enacted via interaction of linguistic and visual resources (Febrian, 2024). Through a combination of sociolinguistic study and digital media approaches, this study will be a part of knowing the role of multilingual, multimodal practices in the formation of online religious identity, emotionality, and community, as applied to the Pakistani context.